2013
DOI: 10.5194/bgd-10-11213-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Calcification intensity in planktonic Foraminifera reflects ambient conditions irrespective of environmental stress

Abstract: Planktonic Foraminifera are important marine calcifiers, and the ongoing change in the oceanic carbon system makes it essential to understand the influence of environmental factors on the biomineralisation of their shells. The amount of calcite deposited by planktonic Foraminifera during calcification has been hypothesized to reflect a range of environmental factors. However, it has never been assessed whether their calcification only passively responds to the conditions of the ambient seawater or whether… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Yet Weinkauf et al (, ) and de Moel et al () found that temperature, upwelling, productivity, and optimum growth conditions influence weight, regardless of changes in CO 2 3 − . Weinkauf et al () suggests that temperature and productivity control SNW in modern Gs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet Weinkauf et al (, ) and de Moel et al () found that temperature, upwelling, productivity, and optimum growth conditions influence weight, regardless of changes in CO 2 3 − . Weinkauf et al () suggests that temperature and productivity control SNW in modern Gs.…”
Section: Discussionmentioning
confidence: 99%
“…This calcification response is more prominent in nonsymbiotic foraminifera than in symbiotic species, which are able to elevate the pH in surrounding waters due to photosynthetic CO 2 fixation (de Nooijer et al, ; Rink et al, ; Wolf‐Gladrow et al, ). The drivers of weight change in foraminifer are still heavily debated as some species and regions show no dependency on the carbonate system suggesting that temperature and productivity drive a change in calcification (Beer et al, ; Weinkauf et al, ; Weinkauf et al, ). For example, reduced salinity may inhibit calcification in some species of foraminifera (Beer et al, ; Bijma et al, ; Weinkauf et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on calibration between SNW in core‐top sediments and bottom‐water Δ[CO 3 2− ] in the equatorial Pacific, size‐normalized test weights have served as a proxy for deep seawater [CO 3 2− ] (e.g., Broecker & Clark, ; Qin et al, ). In contrast, the test area density (μg μm −2 ) of foraminifera, which is the ratio of the weight of a test to its projected area, is a more rigorous size‐standardized proxy than SNW, and it is also employed as a proxy of calcification intensity controlled by sea surface conditions (e.g., Moy et al, ; Weinkauf et al, ; Zarkogiannis et al, ). Sea surface conditions where foraminifera calcify can influence the thickness of foraminiferal test walls (Marshall et al, ) and bulk density (Iwasaki et al, ), which implies that the initial weights of foraminiferal tests differ depending on growth conditions as suggested in Barker and Elderfield (); thus, the test weight proxies SNW and test area density may be affected by not only dissolution at the deep seafloor but also calcification at the sea surface.…”
Section: Introductionmentioning
confidence: 99%
“…Marshall et al., 2013; Weinkauf et al., 2016). In this regard, shell calcification intensity has been mostly used as a proxy for dissolution (Broecker & Clark, 2001; Lohmann, 1995; Schiebel et al., 2007) and marine carbonate system variables (Bijma et al., 1999, 2002; de Moel et al., 2009; Davis et al., 2019; Osborne et al., 2016; Spero et al., 1997; Weinkauf et al., 2013). However, other studies could show that the picture is more complicated and shell calcification intensity is indeed influenced by a variety of environmental factors (Aldridge et al., 2012; Marshall et al., 2013; Mohan et al., 2015; Weinkauf et al., 2016), which may also have an influence on the shell's geochemical composition (e.g., water temperature and salinity; Davis et al., 2016; Gonzalez‐Mora et al., 2008; Zarkogiannis et al., 2019).…”
Section: Introductionmentioning
confidence: 99%